Patient portals: Objectives, acceptance, and effects on health outcome - A scoping review of reviews - Leb, Ines; Magnin, S.; Prokosch, Hans-Ulrich; Boeker, Martin (Studies in Health Technology and Informatics, 2021)
Patient portals provide patients access to their electronic health record and other functions as secure messaging. For over a decade, more and more patient portals are developed for various settings. The aim of this scoping review of reviews is to systematically search the literature for existing reviews to provide an overview of patient portals' objectives, acceptance and effects on outcome. We followed the PRISMA Statement and its extension for scoping reviews, and searched for articles published in 2011 2021. The 19 included articles were considerably heterogeneous concentrating on health outcome or patient portal facilitators and barriers.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Electronic health record; Patient portal; Personal health record; Systematic review